2003
DOI: 10.1029/2002jd002975
|View full text |Cite
|
Sign up to set email alerts
|

Spectral discrimination of coarse and fine mode optical depth

Abstract: [1] The recognition that the aerosol particle size distribution (PSD) is effectively bimodal permits the extraction of the fine and coarse mode optical depths (t f and t c ) from the spectral shape of the total aerosol optical depth (t a = t f + t c ). This purely optical technique avoids intermediate computations of the PSD and yields a direct optical output that is commensurate in complexity with the spectral information content of t a . The separation into t f and t c is a robust process and yields aerosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
589
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 645 publications
(635 citation statements)
references
References 11 publications
13
589
1
4
Order By: Relevance
“…However, AE alone does not provide unambiguous information on the relative weight of coarse and fine modes on the AOD. Several authors have discussed how the spectral variation of the Ångström exponent can provide further information about the aerosol size distribution (Eck et al, 1999;O'Neill et al, 2001aO'Neill et al, , b, 2003Fernández-Gálvez et al, 2013). Kaufman (1993) shows that negative values of the difference =AE 440-613 -AE indicate the dominance of fine mode aerosols while positive values of this difference indicate the effect of two separate particle modes.…”
Section: Introductionmentioning
confidence: 99%
“…However, AE alone does not provide unambiguous information on the relative weight of coarse and fine modes on the AOD. Several authors have discussed how the spectral variation of the Ångström exponent can provide further information about the aerosol size distribution (Eck et al, 1999;O'Neill et al, 2001aO'Neill et al, , b, 2003Fernández-Gálvez et al, 2013). Kaufman (1993) shows that negative values of the difference =AE 440-613 -AE indicate the dominance of fine mode aerosols while positive values of this difference indicate the effect of two separate particle modes.…”
Section: Introductionmentioning
confidence: 99%
“…The size distribution should be ideally split into two parts from centre of the dip. However, we have used a fixed radius of 0.6 µm to separate fine mode and coarse mode AOD as 0.6 µm is the closest to the dip for most seasons and also it is the convention followed for AERONET data (O'Neill et al, 2003). AODs are recalculated for each part separately using the Mie algorithm (Bohren and Huffman, 1983), and the refractive indices and size-distribution retrieved by SKYRAD.…”
Section: Resultsmentioning
confidence: 99%
“…Location of Gadanki is shown with a white star on the map. Air-masses coming from the northeastern direction via the Bay of Bengal are expected to be rich in anthropogenic aerosols whereas the air-masses coming from the Indian Ocean are expected to be rich in natural aerosols (Corrigan et al, 2006;Jayaraman et al, 2006;Suresh Babu et al, 2007;Rajeev et al, 2010).…”
Section: Site-description and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an additional level of refinement of wavelength-dependent measurements of aerosol optical depth (path-integrated extinction) was introduced by to aid in the interpretation of the data obtained by the ground-based sunphotometer networks AERONET and AEROCAN. Specifically, O'Neill et al (2003 showed that the fine-mode fraction (FMF) of extinction and the fine-mode effective radius (R eff,f ) could be extracted directly from the multi-wavelength optical depth or extinction measurements available from remote sensing. The FMF provides for an approximate discrimination between what are typically naturally produced coarse-mode particles (dust or sea spray) and what are often anthropogenically associated fine-mode particles.…”
Section: Introductionmentioning
confidence: 99%